Localising 'radicalisation': Risk assessment practices in Greece and the United Kingdom. (May 2020) - Skleparis, Dimitris; Augestad Knudsen, Rita
This article juxtaposes anti-radicalisation policy in the United Kingdom, one of the pioneers in the field, with Greece, one of the latecomers. Drawing on localisation theory, our aim is to understand how 'common knowledge' of radicalisation and counter-radicalisation has materialised in the United Kingdom and Greece by exploring the development and use of radicalisation-related risk and vulnerability assessment tools. We argue that the radicalisation 'knowledge' was localised more seamlessly in the United Kingdom, which can be attributed to the country's 'norm producer' status on the field of European counter-radicalisation. By contrast, the 'knowledge' was subjected to significant 're-framing' and 'stretching' to fit with the Greek context. This is associated with the country's 'norm adopter' status on the field of European counter-radicalisation, as well as with a 'spill-over effect' from a national context of deeply polarising and contentious counter-terrorism policies. We maintain that these localisation processes reveal two distinct assemblages of governing radicalisation.